J. Hudson Taylor a man in Christ - Steer, Roger, 1945-; China Inland Mission; Overseas Missionary Fellowship (Singapore OMF, 1990)
Includes bibliographical references and index.
Keywords: Taylor, James Hudson, -- 1832-1905; Missionaries -- China -- biography